PENGARUH CUSTOMER VALUE TERHADAP LOYALITAS NASABAH TABUNGAN SIKOCI PADA BANK NAGARI CABANG PADANG PANJANG - yanti, Susri (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2016)
This study aims to see how the influence of customer value (customer value) consisting ofproduct value, service value, and value pricing on customer loyalty savings Sikoci atBranch Bank Nagari Padang Panjang. The population in this study is the savingscustomers Sikoci at Branch Bank Nagari Padang Panjang. Samples taken as many as 100respondents using the technique of Non-Probability Sampling is sampling based on certaintargets. Based on the research results, obtained the following regression equation: Y =3,357 - 0,009X1 + 0,327X2 + 0,172X3. The sequence individually on each of the mostinfluential variable is the variable value of the service with a regression coefficient of0.327, then the variable value pricing with a regression coefficient of 0.172, followed bythe variable value of the product with negative regression coefficient of -0.009. Sedangkais keseluruhukan affect customer value 29.8% based on testing Adjusted R Square. Thismeans that 70.2% of customer loyalty is influenced by other variables.Keywords: Customer Value (Value Product, Service Value, Value Price) CustomerLoyalty.